The results of treatment of chronic recurrent aphthous stomatitis by gel containing zero-valent silver - I. A. Artemieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the results of complex treatment of chronic recurrent aphthous stomatitis by methylcellulose-based gel with arabinogalactan biocomposite containing zero-valent silver in nano-valent condition. The gel was applied 3-6 times a day at the prescription of Diquertin 0,06 g 3 times a day and Fibrolar 0,3g 3 times a day. The proposed method of treatment allows to improve the effectiveness of treatment by increasing remission and reducing treatment terms.